2019
DOI: 10.7554/elife.45946
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ sensor synaptotagmin-1 mediates exocytosis in mammalian photoreceptors

Abstract: To encode light-dependent changes in membrane potential, rod and cone photoreceptors utilize synaptic ribbons to sustain continuous exocytosis while making rapid, fine adjustments to release rate. Release kinetics are shaped by vesicle delivery down ribbons and by properties of exocytotic Ca2+ sensors. We tested the role for synaptotagmin-1 (Syt1) in photoreceptor exocytosis by using novel mouse lines in which Syt1 was conditionally removed from rods or cones. Photoreceptors lacking Syt1 exhibited marked reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 127 publications
(174 reference statements)
10
29
0
Order By: Relevance
“…We affirm the presence of an HCN or i h current activated by hyperpolarization and permeable to both Na + and K + , consistent with the expression of the HCN channels by photoreceptors (Moosmang et al, 2001;Müller et al, 2003). Additionally, our measurements of i Ca are comparable to those recently made by Grassmeyer et al (2019) in both amplitude and voltage dependence. The calcium-activated and voltage-gated conductances we have recorded also have similar properties to those investigated previously (Barnes and Hille, 1989;Xu and Slaughter, 2005;Pelucchi et al, 2008;Stöhr et al, 2009), including in primates (Verweij et al, 2003; but see Yagi and Macleish, 1994).…”
Section: Comparison To Previous Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…We affirm the presence of an HCN or i h current activated by hyperpolarization and permeable to both Na + and K + , consistent with the expression of the HCN channels by photoreceptors (Moosmang et al, 2001;Müller et al, 2003). Additionally, our measurements of i Ca are comparable to those recently made by Grassmeyer et al (2019) in both amplitude and voltage dependence. The calcium-activated and voltage-gated conductances we have recorded also have similar properties to those investigated previously (Barnes and Hille, 1989;Xu and Slaughter, 2005;Pelucchi et al, 2008;Stöhr et al, 2009), including in primates (Verweij et al, 2003; but see Yagi and Macleish, 1994).…”
Section: Comparison To Previous Resultssupporting
confidence: 90%
“…EAATs have been proposed to remove glutamate from the photoreceptor synaptic cleft and to have a critical role in the transmission of the photoresponse (Szmajda and Devries, 2011;Tse et al, 2014). Photoreceptors have been reported to express EAATs (Reye et al, 2002;Hasegawa et al, 2006), which can activate to increase membrane permeability to anions and produce a large change in current during glutamate reuptake from the synaptic cleft (see for example Grassmeyer et al, 2019). We think it unlikely that an EAAT current could have contributed to our measurements of reversal potential in Fig.…”
Section: Contribution Of Electrogenic Transportersmentioning
confidence: 92%
“…The expression of syt1a in the OPL is consistent with the immunofluorescence data in rat and with the finding that synaptic release from photoreceptors in the mouse is largely controlled by synaptotagmin 1 (Grassmeyer et al, 2019). Additionally, the strong syt1a signal detected in the inner half of the INL and in the GCL is very similar to the one for syt1 mRNA in the mouse (Fox & Sanes, 2007).…”
Section: Synaptotagmins Expressed In the Zebrafish Retinasupporting
confidence: 87%
“…Although synaptotagmin 1 Fox & Sanes, 2007;Grassmeyer et al, 2019), synaptotagmin 2 Fox & Sanes, 2007;Neumann & Haverkamp, 2013), synaptotagmin (Butz et al, 1999;Berntson & Morgans, 2003) and synaptotagmin 7 (Luo et al, 2015) have been found in the retina, only synaptotagmin 1 (Grassmeyer et al, 2019) and synaptotagmin 7 (Luo et al, 2015) were reported to modulate different aspects of release in retinal ribbon-containing neurons. Furthermore, synaptotagmin 1 is thought to underlie alone both modes of synaptic transmission in mammalian cone but not rod photoreceptors (Grassmeyer et al, 2019). To date, the synaptotagmins controlling transient and sustained release in bipolar cells are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Rod spherules do demark as U-shaped complexes (e.g., in ribeye 30 or PSD95 31 immunostaining); yet, these usually have their base toward the outer nuclear layer (ONL), which is inverse to what we observed for Kcne2. Horizontal cell neurites are predominantly found in the inner part of the OPL, 31 which is also distinct from where we observed Kcne2 immunoreactivity. With this and the RNA-sequencing results in mind, we think that the none-cone portion of the OPL Kcne2 immunoreactivity indeed arises from rod-BCs.…”
Section: Discussionsupporting
confidence: 60%